From source to sickness: seasonal water risks in Brazil’s Semiarid - Caroline E. Lourenço; Alexandre C. Costa; Tainara C. de Sousa; Adriana M. Silva; João D. Pontes Filho; Caique Ayrton de Brito; Pedro H. A. Medeiros; Eduardo S. P. R. Martins; Rafaella P. Moreira; Pieter R. van Oel (BMC Public Health, 2026)
Abstract Background Limited water access in the Brazilian Semiarid, exacerbated by climate change, increases the risk of diarrheal diseases in rural areas. This study aimed to investigate the seasonal interrelationships between water scarcity, socio-environmental characteristics, water quality, and health outcomes in rural communities. Methods This descriptive field research was carried out in February, April, and September 2025 across three rural communities consisting of households without access to the public water supply network. Data were collected via structured questionnaires and water sampling from all domestic sources used. Hydroclimatic conditions were analyzed to characterize the regional climate scenario. Water quality from different sources was assessed using physicochemical and microbiological parameters. Statistical analyses included the Kruskal-Wallis test with Dunn’s post-hoc test for physicochemical data, Fisher’s Exact Test for microbiological data, and Cochran’s Q and Chi-square tests to evaluate the incidence of diarrhea. Results In 2025, cumulative precipitation decreased in Quixeramobim (-35.2%) and Quixadá (-27.9%) compared to 2024, significantly impacting water source utilization. Families prioritized cisterns for drinking water while utilizing surface reservoirs and wells for hygiene. Water storage in rainfall cisterns fluctuated seasonally and were depleted faster due to inter-household sharing. Physicochemical analyses revealed significant seasonal and inter-community water quality variations, particularly in oxidation-reduction potential (ORP). Comparative analysis showed significant differences across all physicochemical parameters between sources: water tank trucks and the Integrated Rural Sanitation System (SISAR) exhibited higher temperatures and ORP, while wells showed higher alkalinity and electrical conductivity. Microbiologically, widespread total coliform contamination and the persistent presence of E. coli were observed across all sources. However, rainfall cisterns demonstrated the lowest levels of E. coli contamination. Diarrhea cases were reported continuously across the three communities, with 25% of cases affecting children, underscoring the heightened vulnerability of this age group. Conclusions Although cisterns in the semiarid region are relatively safer sources, they are frequently replaced by less reliable alternatives during the dry season, increasing public health risks. Furthermore, storage conditions, domestic water handling, and adaptive strategies in response to water scarcity likely contribute to increased microbiological contamination.